TRANSFORM OR BE REPLACED: AN IN-DEPTH LOOK AT BUSINESS ADAPTATION IN THE AGE OF THE DIGITAL ECONOMY - Taufik Udango; Al-Amin (CV. Adiba Aisha Amira, 2024)
This article explores how businesses must transform to stay relevant and competitive in the digital economy. With the adoption of cutting-edge technologies such as artificial intelligence, data analytics and automation, companies can improve operational efficiency and deliver superior services. However, digital transformation demands not only technological readiness, but also organisational culture change and human resource skill development. On the other hand, businesses that fail to adjust risk losing market share amid intensifying competition. The article also highlights the importance of government support and equitable access to technology for all levels of society and businesses to ensure that all parties can enjoy the benefits of the digital economy.